Repeated measurements of blood lactate concentration as a prognostic marker in horses with acute colitis evaluated with classification and regression trees (CART) and random forest analysis. (July 2016) - Petersen, M.B.; Tolver, A.; Husted, L.; Tølbøll, T.H.; Pihl, T.H.
Highlights: The prognostic value of single and repeated blood measurements was assessed in horses with acute colitis. Lactate, ionised calcium, packed cell volume and plasma protein were investigated. Lactate was the only blood parameter with prognostic value. Classification and regression trees can be used by clinicians in cases of acute colitis. Abstract: The objective of this study was to investigate the prognostic value of single and repeated measurements of bloodl -lactate (Lac) and ionised calcium (iCa) concentrations, packed cell volume (PCV) and plasma total protein (TP) concentration in horses with acute colitis. A total of 66 adult horses admitted with acute colitis (<24 h) to a referral hospital in the 2002–2011 period were included. The prognostic value of Lac, iCa, PCV and TP recorded at admission and 6 h post admission was analysed with univariate analysis, logistic regression, classification and regression trees, as well as random forest analysis. Ponies and Icelandic horses made up 59% of the population, whilst the remaining 41% were horses. Blood lactate concentration at admission was the only individual parameter significantly associated with probability of survival to discharge ( P < 0.001). In a training sample, a Lac cut-off value of 7 mmol/L had a sensitivity of 0.66 and a specificity of 0.92 in predicting survival. In independent test data, the sensitivity was 0.69 and the specificity was 0.76. At the observed survival rate (38%), the optimal decision tree identified horses as non-survivors when the Lac at admission was ≥4.3 mmol/L and the Lac 6 h post admission stayed at >2 mmol/L (sensitivity, 0.72; specificity, 0.8). In conclusion, blood lactate concentration measured at admission and repeated 6 h later aided the prognostic evaluation of horses with acute colitis in this population with a very high mortality rate. This should allow clinicians to give a more reliable prognosis for the horse.